Identification and Analysis of Human Microbe-Disease Associations by Matrix Decomposition and Label Propagation - Qu, Jia; Zhao, Yan; Yin, Jun (Frontiers in Microbiology, 2019)
Studies have shown that microbes exist widely in human body and are closely related to human complex diseases. Predicting potential associations between microbes and diseases is conducive to understanding the mechanisms of complex diseases and can also facilitate the diagnosis and prevention of human diseases. In this paper, we put forward Matrix Decomposition and Label Propagation for Human Microbe-Disease Association prediction (MDLPHMDA) on the basis of the dataset of known microbe-disease associations collected from the database of HMDAD, Gaussian interaction profile kernel similarity for diseases and microbes, disease symptom similarity. Moreover, the performance of our model was evaluated by means of leave-one-out cross validation and 5-fold cross validation, and the corresponding AUCs of 0.9034 and 0.8954+/-0.0030 were gained, respectively. In case studies, 10, 9, 9 and 8 out of the top 10 predicted microbes for asthma, colorectal carcinoma, liver cirrhosis and type 1 diabetes were confirmed by literatures, respectively. Overall, evaluation results showed that MDLPHMDA has good performance in potential microbe-disease associations prediction.